Thermodynamic analysis of ground source heat pump - Khairul Ridhwan, Zainudin (2010)
This thesis describes in detail includes a brief description of the Ground Source Heat Pump as cooling and heating system, concentrating on thermodynamic analysis. Besides, the descriptive drawings make this thesis very easy to understand. The main objective of this thesis is to do thermodynamic analysis on performance of the heat pump system. The changes in cooling water flow will affect the performance of the heat pump system. The value of hole depth and coils length are determine through the equation in chapter 3. In addition to these, this thesis also contains the details regarding the different type of other Ground Source Heat Pump which are used these days. Above all, this thesis gives a detailed description of closed looped Ground Source Heat Pump. This thesis will be help for those who wish to understand about the basic working of different Ground Source Heat Pump especially those who wish to study Ground Source Heat Pump as cooling and heating system.